Analysis Of Completeness And Presentation Of PBL-Based Physics LKPD On Newton's Law Materials To Improve Student's Critical Thinking - Nurul Yunda Nanik Purwanti; Lailatul Firdausiah; Febriana Tri Nur Suliana; Mochammad Ricky Subagya; Thalia Ajeng Ayu Kencana; Nabila Ayu Rosyidah; I Ketut Mahardika; Subiki Subiki (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
This study aims to determine the feasibility of LKPD through validity activities. The research method used is descriptive quantitative research. The data was collected by providing an instrument in the form of LKPD, where the data in this study was in the form of data from the validation results of LKPD. The results of research on the validity of LKPD are based Problem Based Learning it can be seen that the average value of the total validation is 84.38% with a very good category. LKPD Physics based Problem Based Learning in class X Newton's Law material can be said to be valid and can be used as one of the teaching materials to support the physics learning process in accordance with the Independent Curriculum.